Impact of Burnout on Job Psychological Motivation among Correctional Prison Officers in Kenya - Julie Nabwire, Christine; Okoth, George Samuel (Journal of Advanced Psychology, 2025)
Purpose: The reported research sought to examine burnout affects the psychological motivation of correctional officers in their job. Scholars on burnout and psychological work motivation have conducted a significant amount of research. However, only a few studies have investigated the link between burnout and psychological work motivation among these individuals in Kenya. The study was to assess the impact of burnout on job psychological motivation among correctional officers working in six Medium Prisons within Nyanza Region of Kenya. Methodology: This study employed a descriptive and correlational research design utilizing a survey method. The study incorporated both quantitative and qualitative approaches and was guided by the principles of Rational Emotive Behaviour Theory and Solution Focused Theory. The target population was 1,910 prison officers attached to six Medium prisons in Nyanza region of Kenya. The prison facilities included Kisumu Medium Prison in Kisumu County, Nyamira Prison in Nyamira County, Migori Prison in Migori County, Siaya Prison in Siaya County, Kisii Main Prison in Kisii County and Homa Bay Prison in Homa Bay County. The researcher categorized correctional officers into various types of ranks, such as gazetted officers, inspectorate officers, non-commissioned officers, and constables. In this study, the research employed the Maslach Burnout Inventory- Human Services Survey (MBI-HSS) and the Multidimensional Work Motivation Scale (MWMS) as instruments for measurement. Findings: The researcher realized that within the medium prisons, officers who are deployed to work directly with the inmates are male officers whereas the female officers are deployed to work in the offices hence the sample population was totally men. It also came out that there was no difference in the responses from different facilities and therefore the findings were handled generally. The research discovered that burnout has a significantly detrimental effect on the psychological motivation of correctional officers, with a correlation coefficient, r = - 0.768; Sig. = 0.025. Unique Contribution to Theory, Policy and Practice: The research suggests that it would be beneficial for prison management to employ trained counselors and establish effective systems for addressing burnout among correctional officers. Additionally, they should implement methods for increasing the job motivation and psychological well-being of the officers.